2012
DOI: 10.1247/csf.12002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of α-taxilin Localized on Intracellular Components with the Microtubule Cytoskeleton

Abstract: ABSTRACT. Intracellular vesicle traffic plays an essential role in the establishment and maintenance of organelle identity and biosynthetic transport. We have identified α-taxilin as a binding partner of the syntaxin family, which is involved in intracellular vesicle traffic. Recently, we have found that α-taxilin is over-expressed in malignant tissues including hepatocellular carcinoma and renal cell carcinoma. However, a precise role of α-taxilin in intracellular vesicle traffic and carcinogenesis remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…At present, it is not clear how α-taxilin regulates the proper recycling of TfnR. We previously reported that α-taxilin directly interacts with polymerized tubulin [11] and in this study we found that knockdown of α-taxilin decreases the number and length of SNX4-positive tubular structures. Therefore, it is possible that the function of α-taxilin is to connect SNX4-positive tubular structures to microtubules and support the stability of SNX4-positive tubular structures.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…At present, it is not clear how α-taxilin regulates the proper recycling of TfnR. We previously reported that α-taxilin directly interacts with polymerized tubulin [11] and in this study we found that knockdown of α-taxilin decreases the number and length of SNX4-positive tubular structures. Therefore, it is possible that the function of α-taxilin is to connect SNX4-positive tubular structures to microtubules and support the stability of SNX4-positive tubular structures.…”
Section: Discussionsupporting
confidence: 57%
“…We previously demonstrated that α-taxilin is a peripheral membrane protein [11]. We then examined whether the membrane association of α-taxilin depends on interaction with SNX4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations